Reduction in soil CO2 efflux through alteration of hydrothermal factor in milk vetch (Astragalus sinicus L.)-rapeseed (Brassica napus L.) intercropping system - Quan Zhou; Quan Zhou; Quan Zhou; Anna Gunina; Jiao Chen; Yi Xing; Ying Xiong; Zhiming Guo; Longchang Wang (Frontiers in Plant Science, 2023)
IntroductionIntercropping has a potential to reduce the CO2 emission from farmlands. Limited information is available on the underlying reasons.MethodsThis study investigated the effect of milk vetch (Astragalus sinicus L.) (MV), rapeseed (Brassica napus L.) monoculture (RS) and intercropping (Intercrop) on soil CO2 emissions, moisture and temperature in a bucket experiment during 210 days from October 2015 to May 2016 on Chongqing, China.ResultsThe results showed that soil CO2 efflux of MV, RS and Intercrop was 1.44, 1.55 and 2.08 μmol·m-2·s-1 during seedling and stem elongation stages and 3.08, 1.59 and 1.95 μmol·m-2·s-1 during flowering and podding stages. At seeding and stem elongation stages Intercrop had 1.4 times higher soil CO2 efflux than the mean of MV and RS. In contrast, MVhad 1.6 times higher soil CO2 efflux than Intercrop thereafter, which shows it was inhibited if milk vetch presents as Intercrop only. Decreased sensitivity of soil respiration to temperature in 1.4 times and lower soil moisture by Intercrop were found compared to MV. Intercrop decreased soil moisture, especially at the seedling and stem elongation stages, compared to the monoculture. The fluctuation on soil respiration in RS and Intercrop was slight with changes in soil moisture.ConclusionThus, milk vetch-rapeseed system has a potential to decrease CO2 emission from farmland, however soil moisture should be regulated properly.